Bridging Gaps, Building Trust: Comparative Insights into Community Engagement for Public Service Innovation in Makassar City and Sinjay Regency - Haerana, Haerana; Fatmawati, Fatmawati; Lail, Hijrah (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2024)
This research aims to explore the level of community participation in public service innovation and explore the factors supporting this innovation. This type of research uses a mixed method, where in this type of quantitative research, the quantitative method used is cross-sectional with convenience sampling techniques, while qualitative research uses interview and observation data collection methods and is analyzed using Nvivo 12 Plus software. The results of the research show that the level of community participation in Makassar City is that the level of decision making is at the